Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1097/00007890-200108270-00010
|View full text |Cite
|
Sign up to set email alerts
|

Liver Transplantation for Alcoholic Cirrhosis: Long Term Follow-Up and Impact of Disease Recurrence1

Abstract: of cytokine-elicited nitric oxide synthesis in rat liver macrophages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
75
3
8

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(88 citation statements)
references
References 72 publications
2
75
3
8
Order By: Relevance
“…A higher incidence of lung cancer post-LTx with poorer prognosis has been reported by Jiménez et al 44 and others. 41,42,45 In contrast, Haagsma and others did not find any cases of oropharyngeal cancer in their series, 20,24,27,[46][47][48] and only 1 case of oropharyngeal and lung cancer was observed in the present study by Åberg and coworkers, 36 which included 54 cases of alcoholic cirrhosis.…”
Section: Brief Description Of the Differences In The Incidence Of Varcontrasting
confidence: 75%
“…A higher incidence of lung cancer post-LTx with poorer prognosis has been reported by Jiménez et al 44 and others. 41,42,45 In contrast, Haagsma and others did not find any cases of oropharyngeal cancer in their series, 20,24,27,[46][47][48] and only 1 case of oropharyngeal and lung cancer was observed in the present study by Åberg and coworkers, 36 which included 54 cases of alcoholic cirrhosis.…”
Section: Brief Description Of the Differences In The Incidence Of Varcontrasting
confidence: 75%
“…ETOH is a common indication for LT and is associated with very good post-LT outcomes if the patient remains abstinent from further alcohol use. 13 One recent large study showed that survival rates following LT in patients with ETOH are similar to the rates for patients with other causes of cirrhosis (89% versus 84% and 84% versus 81% at 3 and 5 years, respectively). 21 Our results show that although there was a trend toward lower patient survival in the NASH group compared to the ETOH group, the difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 91%
“…Recurrence of the primary disease and/or cardiovascular complications related to the underlying metabolic syndrome may affect the outcome of NASH patients after LT. Alcoholic cirrhosis (ETOH) is a wellestablished indication for LT and is associated with an excellent outcome if the patient remains abstinent from further alcohol use. 13 In this study, using LT for ETOH as a comparator, we assessed the outcomes of LT in patients with cryptogenic cirrhosis with the NASH phenotype.…”
mentioning
confidence: 99%
“…In addition, other studies have reported an increased incidence of the development of chronic hepatitis and allograft failure in HCVpositive patients transplanted for alcoholic cirrhosis. [24][25] It is unclear at this stage how pretransplant alcohol-related liver disease could promote subsequent allograft fibrosis in HCV-infected recipients, and it will be important in future studies to obtain a detailed history of alcohol intake from these patients after transplantation.…”
Section: Discussionmentioning
confidence: 99%